1973
DOI: 10.1139/v73-359
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nucleotides from 8,2′-Thioanhydropurine Nucleosides

Abstract: The 5′-mono and diphosphates of the common 8,2′-thioanhydropurine nucleosides have been prepared and studied with 5′-nucleotidase. alkaline phosphatase, and adenylate kinase. Procedures for the preparation of protected anhydronucleosides and their incorporation into dianhydronucleoside monophosphates have been developed. These nucleotides have been found to be completely resistant to spleen and snake venom phosphodiesterases but are readily converted with Raney nickel into the natural 2′-deoxy-nucleotides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…There have also been two major reports on the incorporation of 8,2'-thioanhydropurine nucleosides into dinucleoside monophosphate units (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have also been two major reports on the incorporation of 8,2'-thioanhydropurine nucleosides into dinucleoside monophosphate units (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Of course there is a significant change in electronic and H-bonding characteristics of 15 as compared to 3. Further it has been observed that the cyclopurine nucleotides are not substrates for either snake venom or spleen phosphodiesterases (20). In the cyclopurines the base is constrained in a near anti conformation.…”
mentioning
confidence: 99%